Aktivitas Rantai Pasok Usaha Pengolahan Kopi Arabika Kintamani Berbasis SCOR Pada Unit Pengolahan Hasil Catur Paramita - DEWI, IDA AYU LISTIA; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
SCOR-Based Kintamani Arabica Coffee Processing Business Supply Chain Activities at the Catur Paramita Processing Unit.  The objectives of this research are 1. to describe the mechanism of activity in the UPH Catur Paramita Arabica coffee processing supply chain using the SCOR approach. 2. Measuring the performance of SCOR-based Arabica coffee processing supply chain activities at UPH Catur Paramita. The research location was determined using a purposive method with the consideration that Catur Village is the center of Balinese Arabica coffee production and is the only UPH in Catur Village that continues to collaborate with farming community institutions. This research is qualitative. Qualitative data is obtained directly from primary data, including planning, procurement, production, and distribution processes. The sampling method is snowbolling sampling, and the starting point is the processing industry. Data analysis was carried out using qualitative descriptive methods. The research results show that written planning and other records have yet to be carried out continuously. There are no harvest timings yet, which creates further problems for UPH Catur Paramita. Evaluation and supervision of the implementation of standard production procedures are not carried out regularly. The delivery document is in the form of a purchase receipt. Returns of damaged products have yet to be fully documented. Four activities that need improvement by UPH Catur Paramita, namely plan, make, and return, each of which is very poor. Source activity is in the poor category.